التقدير الكمي والتنقية الجزئية لمركبي الفنبالستين و الفنكرستين لثالثة نباتات من العائلة الدفلية Apocynaceae - هادي, صباح مهدي; حتيت, واثق عباس (Al-Nahrain Journal of Science, 2018)
This study was carried out on three Apocynaceae family plants namely, Nerium oleander, Thevetia peruviana and Carissa grandaiflora. Thin layer chromatography TLC, column chromatography and high performance chromatography HPLC were used for identification, partial purification and quantities determination for Vinblastine and Vincristine compounds. Results showed that the highest concentration was 4.35ppm/o.5 g d.w. for Vinblastine in leaves extract of Thevetia peruviana and 3.725 ppm /o.5 g d.w. in leaves extract of Nerium oleander and 0.893 ppm /o.5 g d.w for Vincristine in leaves extract of Carissa grandaiflora. TLC: Thin layer Chromatography HPLC: High performance liquid Chromatography Rf: Retardation Factor VIB: Vinblastine VIC: Vincristine